From perception to imitation in the accessibility of older adults in web interfaces (2019)
Older adults, who are a growing population in Colombia and the world, are using more often web interfaces and other digital technologies. Although there are several references about how to create usable and accessible web interfaces, they focus on perceptual limitations. One of the factors of disability in older adults are the cognitive limitations, such as memory problems, which are the main factor that reduces accessibility. This article is a report of an exploratory study that identified the experiences and interactions with 12 seniors, who participated in a focus group or a usability test and interview. In addition to identifying types of content in the web of the older adults (in their order are: health, entertainment —music—, and news), the authors detected vicarious learning or by imitation, which is a core social cognitive process that can generate greater accessibility. By observing a similarperson conducting activities, the elderly as an observer also perceives a capacity to perform them by imitation (self efficacy).